ON THE MOLDOVAN ECONOMY’S POTENTIAL OUTPUT AND OUTPUT GAP: EVIDENCE FROM THE HODRICK-PRESCOTT FILTER - Apostolos Papaphilippou (Economy and Sociology)
This paper introduces the notion of an economy’s potential output, its output gap and its output gap rate, analyses the properties of the Hodrick-Prescott filter drawing from the studies in the literature, and proceeds to estimate and discuss Moldova’s potential output, its output gap and its output gap rate utilising a methodology which can be used in other economies. The data for our empirical work comprise annual data on: 1. Moldova’s nominal GDP and the annual rate of growth or real GDP over the period 2010-2022; and 2. The latest forecasts of these indicators for the period 2023-2026. Data earlier than 2010 are not comparable as they were compiled under a different methodology. We use this data set to generate a time series of the evolution of Moldova’s real GDP in average prices of 2010 over the period 2010-2026. We apply the Hodrick-Prescott filter with the two different values of the filter’s smoothing parameter suggested by the studies in the literature for the decomposition of annual data. As it is well-known that the estimates of the filter are sensitive to the value of the smoothing parameter, we use the average of the two estimates in order to calculate the Moldovan economy’s potential output, output gap and output gap rate through time. Our calculations suggest that, over the period analysed, Moldova’s potential output has grown at a modest rate which is not sufficient for the country to converge to the EU average and attain its EU aspirations. The paper concludes by discussing a number of recent economic developments in Moldova, the required policy response to attain Moldova’s EU aspirations and areas for further work.